DOES BEHAVIOUR‐BASED PRICE DISCRIMINATION FOSTER FIRMS' DIFFERENTIATION?. (4th May 2016) - Colombo, Stefano
ABSTRACT: We study the impact of behaviour‐based price discrimination on the incentive of the firms to differentiate their products. We consider both 'standard' and 'extreme' behaviour‐based price discrimination: the latter always reduces the incentive to differentiate with respect to uniform pricing, while the former fosters differentiation if the consumers are sufficiently forward‐looking and/or the firms are sufficiently myopic.